Self‐Mineralized Photothermal Bacteria Hybridizing with Mitochondria‐Targeted Metal–Organic Frameworks for Augmenting Photothermal Tumor Therapy - Chen, Qi‐Wen; Liu, Xin‐Hua; Fan, Jin‐Xuan; Peng, Si‐Yuan; Wang, Jia‐Wei; Wang, Xia‐Nan; Zhang, Cheng; Liu, Chuan‐Jun; Zhang, Xian‐Zheng (Advanced functional materials, 2020)
A photothermal bacterium (PTB) is reported for tumor‐targeted photothermal therapy (PTT) by using facultative anaerobic bacterium Shewanella oneidensis MR‐1 (S. oneidensis MR‐1) to biomineralize palladium nanoparticles (Pd NPs) on its surface without affecting bacterial activity. It is found that PTB possesses superior photothermal property in near infrared (NIR) regions, as well as preferential tumor‐targeting capacity. Zeolitic imidazole frameworks‐90 (ZIF‐90) encapsulating photosensitizer methylene blue (MB) are hybridized on the surface of living PTB to further enhance PTT efficacy. MB‐encapsulated ZIF‐90 (ZIF‐90/MB) can selectively release MB at mitochondria and cause mitochondrial dysfunction by producing singlet oxygen (1O2) under light illumination. Mitochondrial dysfunction further contributes to adenosine triphosphate (ATP) synthesis inhibition and heat shock proteins (HSPs) down‐regulated expression. The PTB‐based therapeutic platform of PTB@ZIF‐90/MB demonstrated here will find great potential to overcome the challenges of tumor targeting and tumor heat tolerance in PTT. A bacteria‐based photothermal therapeutic platform comprising PTB@ZIF‐90/MB is developed, which reveals great potential to augment photothermal therapy efficacy by tackling the challenges of tumor targeting and heat resistance.